Exploring the effect of BN and B-N bridges on the photocatalytic performance of semiconductor heterojunctions: Enhancing carrier transfer mechanism. (September 2021) - Coy, Emerson; Siuzdak, Katarzyna; Grądzka-Kurzaj, Iwona; Sayegh, Syreina; Weber, Matthieu; Ziółek, Marcin; Bechelany, Mikhael; Iatsunskyi, Igor
Highlights: TiO2 /ZnO surfaces have been coated with Boron Nitride by Atomic Layer Deposition. Higher photoresponse (170%) and a widening in the bandgap (9%) is observed. A first-order decay rate of 3.4 ns -1 is measured for BN composites. Enhancement is related to the B-N-(Metal Oxide) bridges on the samples. BN by ALD is an effective method for enhancing the photoactivity of semiconductors. Abstract: Several strategies are currently available to improve the photocatalytic response and performance of materials and devices. Despite this, the most common strategies are still based on the promotion of efficient carrier transfer/lifetime of photo-exited electrons and bandgap tailoring. In this work, we present conclusive experimental evidence of the synergistic effect of Boron Nitride (BN) and B-N bridges on the carrier transfer efficiency of photogenerated species. We present a simple method for exploiting both approaches by the incorporation of B-N bridges on TiO2 /ZnO heterojunctions by Atomic Layer Deposition (ALD). We show the improved lifetime of holes by the integration of B-N bridges, as shown by the very low first-order recombination times 3.4±1.2 ns −1, and the superior photoresponse of the composites, with a strong increment of 170% observed in transient photocurrent studies and supported by the incident photon to current efficiency. Also, the TiO2 /ZnO/BN heterojunction presents an 82% in photodegradation of contaminants ( k =7.84*10 −3 min −1 ). Finally, we provide experimental evidence of the hole extracting role of BN and bring a general strategy for integration of B-N bridges by ALD conformal coating capabilities. We believe that the results open up the possibility for exploitation in several architectures, materials, and devices by in-situ preparation of efficient carrier transfer layers by ALD. Graphical abstract: Image, graphical abstract